Criminal Acts of Sexual Harassment in the City of Makassar from a Criminological Perspective - Fajran; Nur Fadhillah Mappaselleng; Asriati Asriati (Faculty of Law, Universitas Muslim Indonesia, 2025)
This study aims to examine the factors contributing to the occurrence of sexual harassment crimes in Makassar City and to analyze the efforts undertaken for their prevention and control. The research employs an empirical approach, with the research location at the South Sulawesi Regional Police (Polda Sulsel). The types and sources of data consist of primary, secondary, and tertiary data, which were collected through interviews and documentation. The collected data were subsequently analyzed using qualitative analysis. The findings indicate that the factors contributing to sexual harassment crimes in Makassar City include environmental factors, peer association factors, and economic factors. Preventive and control measures implemented by the South Sulawesi Regional Police involve firm law enforcement accompanied by public education and legal literacy programs related to sexual harassment, as well as legal awareness campaigns addressing its forms, impacts, and legal consequences. In terms of countermeasures, efforts include the provision of legal protection, medical assistance, and social rehabilitation for victims of sexual harassment. Based on these findings, this study recommends that law enforcement officers be provided with gender- and victim-sensitive training to ensure professional, empathetic, and fair handling of sexual harassment cases without blaming or marginalizing victims. Furthermore, the police are encouraged to develop more accessible reporting mechanisms, such as dedicated hotlines or mobile-based applications, to enable victims to report incidents safely while ensuring confidentiality.